2016
DOI: 10.12693/aphyspola.130.362
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Magnetic Properties of Ca-Doped Mn-Ferrite

Abstract: Spinel ferrite structures have vast applications, from microwave to radio frequencies. In order to acquire new electronic and optical behavior, divalent cations can be added to normal spinel ferrite structure. This way it is possible to facilitate its usage in material and science technology. In this work we have analyzed the impact of Ca addition to normal spinel manganese ferrite on electronic and magnetic properties by the first-principles calculations. For the exchange-correlation functional, Wu-Cohen, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…The total DOS structure of MnFe2O4 and Ca-MnFe2O4 is given in Figure 5, which shows the similar band structure in spin-down states, while the band gaps of MnFe2O4 (1.6 eV) and Ca-MnFe2O4 (2.3 eV) are mainly determined by spin-up states. The total magnetic moment of the unit cell and total magnetic moment of the formula unit both decrease with the addition of Ca to MnFe2O4 (110.29 µB to 93.63 µB) and (13.78 µB to 11.70 µB), respectively [11], as shown in Table S1, which shows close agreement with the experimental results. As represented in Scheme 2 (i−v), the Cat (II) was activated in the presence of molecular oxygen to produce Cat (III)-OO˚, where (II) and (III) show the oxidation states.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…The total DOS structure of MnFe2O4 and Ca-MnFe2O4 is given in Figure 5, which shows the similar band structure in spin-down states, while the band gaps of MnFe2O4 (1.6 eV) and Ca-MnFe2O4 (2.3 eV) are mainly determined by spin-up states. The total magnetic moment of the unit cell and total magnetic moment of the formula unit both decrease with the addition of Ca to MnFe2O4 (110.29 µB to 93.63 µB) and (13.78 µB to 11.70 µB), respectively [11], as shown in Table S1, which shows close agreement with the experimental results. As represented in Scheme 2 (i−v), the Cat (II) was activated in the presence of molecular oxygen to produce Cat (III)-OO˚, where (II) and (III) show the oxidation states.…”
Section: Methodssupporting
confidence: 83%
“…Crystals 2020, 10, x FOR PEER REVIEW 10 of 17 up state of MnFe2O4 up to (0.7 eV), as shown in Figure 4a, while Ca doping up to 20% decreased the band gap energy by 0.22 eV. Ustundağ et al [11] have also reported that the band gap energy of MnFe2O4 is reduced by the incorporation of calcium. The Density of States (DOS) structure of MnFe2O4 and Ca-MnFe2O4 is presented in Figure 4b, which reveals that the Fe atom has a paramount impact on DOS structure for MnFe2O4; similarly, Fe and Mn atoms have a great impact, while Ca contribution is too low in the DOS structure for Ca-MnFe2O4.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…This type of spinel is a promising conductingprotective material, since it exhibits good electrical conductivity and high density, is a good barrier against the diffusion of chromium ions, and the cost of the starting materials required to obtain is not overly high [4].…”
Section: Introductionmentioning
confidence: 99%
“…Laslouni et al [5] studied magnetic properties and resistivity measurement of nanocrystalline Cu 70 Fe 18 Co 12 alloys. Ustundağ and Aslan [6] investigated electronic and magnetic properties of Ca-doped Mn-ferrite. Boubaker and Said [7] reported the structural, elastic and mechanical properties of Mn 3 Sb intermetallic compound by using ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%